If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 10 = 6t Reorder the terms: 10 + -4y = 6t Solving 10 + -4y = 6t Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -4y = -10 + 6t Combine like terms: 10 + -10 = 0 0 + -4y = -10 + 6t -4y = -10 + 6t Divide each side by '-4'. y = 2.5 + -1.5t Simplifying y = 2.5 + -1.5t
| -6(9-8x)=36 | | 4x/8=5/2 | | 6×4/12 | | 4x/40=5/2 | | 114=6(1-6p) | | (4x+23)+26+29=180 | | 3xy*7x= | | 49a^3+14a^2-14a-4=0 | | ((3n-6)n)/(-2(n-2)) | | 11p^2+24p+4=0 | | ((3n-6)n)/(-2(n-2) | | 3y=2+5 | | 6x+6-4x=6+2x | | f(3a-9)=(-3x+11) | | 4=4n-2n | | 2(1.5z+3.5)=16.0 | | P×3/10=3/4 | | 10=6a+4a | | 4x/13=5/2 | | 4(2.1z+2.75)=-14.2 | | 3x+ky=5 | | 8=3n+4+4 | | 1000-r=99.52 | | (3x+y)=(2x+y) | | 0=6cos(x) | | 2(6x+4)=44 | | 12=4k+6+2k | | 1931+x=4734 | | 2+y=4-6 | | 26-5-12+6= | | 6(r-4)-5r=-13+2 | | 5x/3=8/3 |